OBESITY AS A RISK FACTOR FOR REPRODUCTIVE DYSFUNCTION IN WOMEN - Boborakhimova, U.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction. The aim of the study is to assess the prevalence and characteristics of the clinical and metabolic profile of obesity and metabolic syndrome in women of reproductive age. Material and methods of the study. Based on the goals and objectives of the study, we studied the patients’ medical history, age, obesity etiology, clinical picture and treatment results. In addition, to determine the quality of life and the impact of complaints on it, a special questionnaire was filled out to assess eating behavior. A total of 150 women of reproductive age with overweight/obesity were examined. According to the type of obesity, 88 (58.7%) women belonged to the female type, 62 (41.3%) women to the android type. Results of the study Each participant underwent: questionnaire (anamnesis, lifestyle, complaints, menstrual cycle); measurement of height, weight, waist and hip circumference; calculation of BMI and WC/HC ratio; measurement of blood pressure; biochemical analyses: glucose, insulin, HOMA-IR index, total cholesterol, LDL, HDL, triglycerides; determination of hormonal profile (FSH, LH, estradiol, testosterone, DHEA-s). We measured leptin levels for differential diagnostics of obesity with leptin resistance in 150 women of reproductive age with overweight/obesity aged 18 to 35 years Conclusions. Obesity and metabolic syndrome are widespread among women of reproductive age and are accompanied by pronounced disturbances in carbohydrate, lipid and hormonal metabolism. Metabolic disturbances significantly increase the risk of menstrual dysfunction, infertility and complicated pregnancy. Screening for metabolic syndrome, insulin resistance, and hyperandrogenism should be performed in all overweight women, especially in the presence of menstrual irregularities.